ANALISIS MASALAH KESEHATAN DI KABUPATEN SUKOHARJO TAHUN 2010 - Wibowo, Yudhi; AP, Wisnuwijoyo (MANDALA of Health, 2014)
In order for any program capable of reaching targets optimally , it requires good planning . One step that must be taken is to do a Community Health Analysis (CHA). The goal of CHA is to obtain an overview status of public health in the working area of the District Health Office Sukoharjo , Central Java Province in 2010 . This study was a descriptive observational by analyzing secondary data of Sukoharjo Health Department . How to determine the priority of the problem with the Hanlon method using four criterias : 1 ) The magnitude of the problem ; 2 ) the urgency of the problem ; 3 ) Ease of countermeasures ; 4 ) PEARL factor. Identified health problems in 2010 is maternal mortality 152.28/100.00 Live Births (LB) (target 80.41/100.000 LB) , incidence rate (IR) of DHF 51.59/100,000 population (target < 20/100.000 population ) , Case Fatality Rate (CFR) of DHF 2.3 (target <1 ) , Case Detection Rate (CDR) Acid-Fast Bacilli smear (+) 25.91 % (target 85%) , diarrhea coverage which handled 94.7 % (target 100 % ) , 567 cases of chikungunya cases is still high , the UCI 92.22 % (target 100 %) , 1 leptopsirosis new cases , 1 case comfirm AI died , the number of HIV/AIDS increased from 7 cases (2009) to 12 (2010), the incidence of stroke increased from 3,417 cases (2009) to 3,481 (2010), essential hypertension is highest prevalence of NCDs group is 35 028. The order of priority of the problem is 1) IMR ; 2) DHF ; 3) Immunization ; 4) AI ; 5) TB ; 6) Type II DM and 7) Essential Hypertension . Maternal & Child Health program is a priority issue for IMR that exceeded the national target, infectious disease dengue, AI, tuberculosis and NCDs is Type II DM and essential hypertension is also a health issue. The cause of the problem related to environmental factors and behavioral and community empowerment.